PANDUAN GERAKAN DASAR PENCAK SILAT MELALUI MEDIA BUKU ILUSTRASI - Fajri Junfikar; syafwandi syafwandi (Universitas Negeri Padang, 2020)
The purpose of writing this article is to make a martial arts guidebook with language and illustrations that are easily understood by the target audience, namely children. This guidebook is also a supporting medium in the implementation of martial arts activities that are suitable for children because they are in their growth and development. The reason why this book was made is in the available pencak silat books, which are still dominated by written forms which are not very effective for children to learn pencak silat. Approach to the design of the basic pencak silat manual book design covers the design of books, pencak silat, illustrations, colors, layouts, and typography.The design method used to design the Pencak Silat Basic Movement Guidelines is a glass box method based on data obtained through observation, interviews and literature studies on books and pencak silat. Data were analyzed using the 5W1H method, which are what, who, where, why, when and how.The article output of the Pencak Silat Basic Movement Guidance Book produced a primary medium in the form of a conventional guidebook. The supporting media produced were Poster, Sticker, Pin, X-Banner, Tumbler, Totebag, T-Shirt, and E-Book.Keywords: Book, Illustration,Pencak Silat